Pelaksanaan Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Terhadap Peningkatan Pendapatan Asli Daerah Di Kota Langsa - Safrizal Wahyudi; Muhammad Abduh; Faisal Akbar; Jusmadi Sikumbang (Universitas Sumatera Utara, 2019)
Abstract. The regional authority in collecting taxes and levies is regulated by Law No. 28 of 2009 concerning Regional Taxes and Regional Levies. Based on this law, regions are given the authority to collect 11 types of taxes and 33 types of user fees, with the consideration that these types of taxes and user charges are generally good. This research is used normative legal research method. Normative legal research is research by only processing and using secondary data relating to the issue of